Does Non-Placement of a Drain in Breast Surgery Increase the Rate of Complications and Revisions? - Ebner, F. K.; Friedl, T. W. P.; deGregorio, N.; Reich, A.; Janni, W.; Rempen, A. (Geburtshilfe und Frauenheilkunde, 2013)
Purpose: Although surgical therapy for breast cancer has become less radical, intrasurgical placement of drains and the use of compression bandages is still standard practice. However, evidence for the clinical benefit of wound drains is controversial, and use of drains is associated with increased pain and longer hospital stays. This raises the question whether, given the latest surgical techniques, wound drainage is still medically necessary.Material and Method: A retrospective analysis was done of patients with breast cancer treated surgically between January 2009 and April 2012 in the Breast Centre Hohenlohe (n = 573). Complication rates and revision following surgery with and without placement of wound drains were compared for patients who had breast-conserving surgery (n = 425) and patients who underwent mastectomy (n = 148).Results: The baseline characteristics (age, number of resected lymph nodes, numbers of patients who had sentinel lymph node resection, tumour characteristics, receptor status and affected side) were comparable for the investigated patient groups. The overall rate of complications was 4 %. There was no significant difference with regard to complication rates after surgery with and without placement of wound drains between the group of patients with breast-conserving surgery and the group of patients with mastectomy (p = 0.68 and p = 0.54, respectively).Conclusion: Our data indicate that non-placement of a wound drain does not influence complication or revision rates after breast-conserving surgery or mastectomy.
Keywords: breast cancer; breast; breast malignancy; complication; drainage; seroma